Integration or Outsourcing: Combining Ex Ante Distortions and Ex Post Inefficiencies - Verena Nowak (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Final good production often requires a firm's headquarter services and a foreign supplier's manufacturing input. With incomplete contracts, firms that decide whether to choose integration or outsourcing of this supplier do not only have to consider the ex ante investment incentives that influence the own and the supplier's underinvestment problem. Instead, firms also have to take into account the risk that the supplier cribs the knowledge and ex post becomes a competitor for the final good. With exogeneous risk of ex post inefficiencies associated with one particular organizational form, this organizational form becomes less likely. However, considering the supplier's incentives to become a competitor, integrated supplier have a higher risk of ex post inefficiencies. Hence, the consideration of ex post inefficiencies makes outsourcing more likely.
Keywords: D23; D86; L22; 330